Energy efficiency analysis considering the use of an intelligent systems management in a smart home - Morais, H. (2013)
In this abstract is presented an energy management system included in a SCADA system existent in a intelligent home. The system control the home energy resources according to the players definitions (electricity consumption and comfort levels), the electricity prices variation in real time mode and the DR events proposed by the aggregators.